Racing the Great White Way Black Performance, Eugene O'Neill, and the Transformation of Broadway - Johnson, Katie N. (Theater: Theory/Text/Performance, 2023)
The early drama of Eugene O'Neill, with its emphasis on racial themes and conflicts, opened up extraordinary opportunities for Black performers to challenge racist structures in modern theater and cinema. By adapting O'Neill's dramatic writing-changing scripts to omit offensive epithets, inserting African American music and dance, or including citations of Black internationalism--theater artists of color have used O'Neill's texts to raze barriers in American and transatlantic theater. Challenging the widely accepted idea that Broadway was the white-hot creative engine of U.S. theater during the early 20th century, author Katie N. Johnson reveals a far more complex system of exchanges between the Broadway establishment and a vibrant Black theater scene in New York and beyond to chart a new history of American and transnational theater. In spite of their dichotomous (and at times problematic) representation of Blackness, O'Neill's plays such as The Emperor Jones and All God's Chillun Got Wings make ideal case studies because of the way these works stimulated traffic between Broadway and Harlem-and between white and Black America. These investigations of O'Neill and Broadway productions are enriched by the vibrant transnational exchange found in early to mid-20th century artistic production. Anchored in archival research, Racing the Great White Way recovers not only vital lost performance histories, but also the layered contexts for performing bodies across the Black Atlantic and the Circum-Atlantic.